Removal of taste and odor model compound (2,4,6-trichloroanisole) by tight ultrafiltration membranes - Park, Noeon; Lee, Yonghun; Lee, Seockheon; Cho, Jaeweon (ELSEVIER SCIENCE BV, 2007)
Taste and odor causing organic compounds of concern to the general public are produced at low concentrations (i.e., ng/L) in surface water. Bench-scale membrane filtration experiments were conducted with 2,4,6-trichloroanisole (TCA), which is of special interest as a model compound due to its very low odor threshold level (i.e., 10 ng/L). Four different tight ultrafiltration (UF) membranes, with different molecular weight cutoffs (MWCO) and hydrophobicities were investigated. The removal of TCA decreased with increasing permeability for all of the UF membranes tested. Relatively hydrophobic UF membranes, even those with higher MWCO and permeability values, exhibited much higher TCA removal efficiencies than relatively hydrophilic UF membranes, both in the presence and absence of hydrophobic natural organic matter (Suwannee River NOM). The adsorption of TCA onto the membrane surfaces/pores through the hydrophobic interaction was found to be important for the efficient removals of TCA by hydrophobic UF membranes, especially those with greater hydrophobicities. The removals of TCA by the tight-UF membranes were affected by two major mechanisms: (1) a convection mechanism for the transmission of TCA through the membrane pores and (2) the adsorption of TCA onto the membrane surfaces/pores through hydrophobic interactions.
Keywords: DRINKING-WATER; GEOSMIN; NOM; MIB